EVALUATION OF APICAL DEBRIS EXTRUSION OF THREE NI-TI ROTARY FILE SYSTEMS: AN IN VITRO STUDY - Amna Riaz; Kiran Saba; Ayousha Iqbal; Sana Jalil Hassan; Beenish Qureshi; Hufsa Siddiqui (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The advent of nickel-titanium (Ni-Ti) instruments has revolutionized root canal treatment, offering enhanced flexibility and strength. Despite these advantages, there remains a risk of instrument fracture and debris extrusion, which can compromise treatment outcomes. Objective: To evaluate and compare the amount of apically extruded debris among Protaper Next, XP-3D EndoShaper, and WaveOne file systems. Study Design: Experimental study: Quasi-randomized controlled trial. Setting: Department of Operative Dentistry, University of Lahore. Department of Operative Dentistry, Dental College HITEC-IMS, Taxila. Department of Operative Dentistry, Islamabad Medical and Dental College, Islamabad Study Duration: Eight months following synopsis approval. Materials and Methods: Sample Size: 60 samples (20 in each group). Groups: • Group A: Protaper Next • Group B: XP-3D EndoShaper • Group C: WaveOne Ni-Ti rotary file system Procedure: Samples were assessed for apical debris extrusion. Data were analyzed using SPSS version 23 with Paired sample T-test and ANOVA. A p-value of ≤0.05 was considered significant. Results: XP-3D EndoShaper demonstrated significantly lower debris extrusion (0.0028±0.002SD) compared to Protaper next (0.007945±0.0001SD) and WaveOne (0.0048±0.0008SD) (P=0.000). Conclusion: All Ni-Ti rotary systems evaluated were safe for use, but the XP-3D EndoShaper exhibited the lowest level of debris extrusion, suggesting its superior performance in minimizing post-operative complications.